Politics, knowledge, and sexual assault: public perceptions of Trump-era Title IX proceedings. Issue 1 (1st January 2023) - Mancini, Christina; Cassino, Dan; Lytle, Robert D.
ABSTRACT: In 2020, the Trump administration issued new guidance concerning Title IX proceedings; one controversial change was the emphasis on greater confrontation between complainants and respondents during the grievance process. Little is known concerning public perceptions of these reforms, which diverge from previous federal guidance. To that end, we explore three questions. First, to what extent was the public aware of changes to Title IX? Second, does the public think colleges can safely implement confrontational grievance procedures, or do they view such proceedings skeptically? Last, what factors are associated with beliefs about confrontational features of Title IX? Analysis indicates that there are conditional effects of political ideology on levels of knowledge about the Title IX changes on attitudes toward grievance proceedings. Additionally, other demographic correlates – age, sex, and educational attainment – are associated with perceptions. Implications are discussed.